Mekanisme Pelaksanaan Peraturan Pemerintah Nomor 23 Tahun 2018 Terhadap CV Djanti Medika di Bekasi Pada Tahun 2021 - NingTyas, Indriani Rahayu; Utami, Noviandari Sari; Agustina, Dwi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Government regulation number 23 of 2018 which is an amendment to government regulation number 46 of 2013 focuses on research on corporate taxpayers CV Djanti Medika in Bekasi in 2021 regarding tariff changes. The purpose of this observation is to find out the implementation of government regulations CV Djanti Medika for the 2021 period starting from calculation, deposit, and reporting based on the applicable Tax Regulations.The legal basis for Government Regulation number 23 of 2018, Minister of Finance Regulation number 99/PMK.03/2018, and Article 3 paragraph (3) letter c UU KUP. The method used is a qualitative method, data collection techniques by observation and interviews with employees of the tax consultant CV Djanti Medika. The results of observations that occurred at CV Djanti Medika in 2021 were that there was an administrative fine of 2% due to delays in reporting every month. The results obtained in the implementation of government regulation No. 23 of 2018 are not fully in accordance with the applicable laws and regulations.